Buckling Instability Control of 1D Nanowire Networks for a Large‐Area Stretchable and Transparent Electrode. (17th March 2020) - Kim, Byoung Soo; Kwon, Hyowon; Kwon, Hyun Jeong; Pyo, Jun Beom; Oh, Jinwoo; Hong, Soo Yeong; Park, Jong Hyuk; Char, Kookheon; Ha, Jeong Sook; Son, Jeong Gon; Lee, Sang‐Soo
Abstract: A commonly used strategy to impose deformability on conductive materials is the prestrain method, in which conductive materials are placed on prestretched elastic substrates and relaxed to create wavy or wrinkled structures. However, 1D metallic nanowire (NW) networks typically result in out‐of‐plane buckling defects and NW fractures, due to their rigid and brittle nature and nonuniform load transfer to specific points of NW. To resolve these problems, an alternative method is proposed to control the elastic modulus of 1D NW networks through contact with various solvents during compressive strain. Through solvent contact, the interface interactions between the NWs and between the NW and substrate can be controlled, and it is shown that the surface instability of the 1D random network is formed differently from a uniform bilayer film, which also can vary with the modulus of the network. For modulus values lower than the critical point, slippage and rearrangement of NW strands mainly occur and individual strands in the network show an in‐plane wavy configuration, which is ideal for structural stretchability. Based on the solvent‐assisted prestrain method, letter‐sized, large‐area stretchable, and transparent electrodes with high transparency and conductivity are achieved, and stretchable and transparent alternating current electroluminescent devices for stretchable display applications are also realized. Abstract : The surface instability structure of a 1D nanowire random network can be controlled by solvent annealing under compressive strain. For lower than the critical point, slippage and rearrangement into in‐plane wavy configuration of nanowire strands mainly occurs, which is ideal for structural stretchability. Based on this phenomenon, large‐area stretchable and transparent electrodes with high transparency and conductivity and stretchable and transparent alternating current electroluminescent devices can be realized.